THE CELEBRATION OF THE CULT OF ST. JOHN VLADIMIR IN THE BALKANS - Maja Jakimovska-Tosic (Philological Studies, 2019)
The research is directed toward the mainstream Balkan celebration of the cult of St. John Vladimir, a celebration which is widespread in the Balkans. It is important to underline the forms of its manifestation, which may contribute to the construction of the Balkan world outlook, a general idea of the background of certain common religious manifestations and cultural phenomena. Such saints figures played the role of overriders of the impatience that exist between the Balkan nations and has enabled a coexistence in a kind of "syncretism."